El gobierno de la Unidad Popular en Chile y la prensa costarricense, 1970-1974 - Arce Valverde, Luis Gerardo (2020)
UCR::Docencia::Ciencias Sociales::Facultad de Ciencias Sociales::Escuela de Historia